Путешествие Алисы: повесть / Кир Булычев - Булычев Кир (Библиотека школьника, 2022)
Экземпляры: ф.4 (20240604) / Инвентарный номер: 1208 / Цена: / Сис.шифр: 84(2=411.2)6-4 / Авт.знак: Б 90 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)6-445.1